Rancang Bangun Kios Minuman dengan Konsep Container Booth Bertenaga Surya - Suhono, Suhono; Hakim, Arif Lukman; Aqmarina, Nur; Oktiawati, Unan Yusmaniar; Subekti, Lukman; Pradana, Adlan Bagus; Slamet, Slamet; Ulung, Ridwan Printis (Jurnal ELTIKOM : Jurnal Teknik Elektro, Teknologi Informasi dan Komputer, 2022)
Energy access is still limited to several areas with the criteria of being remote, underdeveloped, outermost (3T). In addition, limitations still occur in areas considered less economical if an electrical system or network is built. Therefore, there is a need to implement solar panel technology that can improve the economy of the people in areas with these limitations. The objectives of this study are threefold. First, to design a beverage kiosk with a container booth concept where its energy needs are met using solar panels. Second, to analyze the energy con-sumption ratio between direct current (DC) and alternating current (AC) electricity systems when used to meet the needs of the container booth. Third, to analyze the potential for reducing carbon emissions through the use of solar-powered container booths. This research was conducted by analyzing the initial energy requirements through a survey on existing container booth users. The system design is carried out and tests the energy produced by solar panels and the energy consumed for beverage processing. The total energy produced and the potentials for emission reduction were analyzed from each system's test data (DC and AC). The AC system has an efficiency of 21.11%, while the DC system has 19.08%. In terms of battery usage for one day of use, the AC system will reduce 12.03% of the battery while the DC system is 14.34%. The analysis shows that this solar-powered beverage kiosk can meet operational energy needs for two days and reduce emissions equivalent to 34.82 to 58.84 kg of CO2. This concept is expected to be an alternative for society.